EKSPLORASI CONTENT KNOWLEDGE MAHASISWA CALON GURU PADA MATERI SISTEM PERIODIK UNSUR - Andari Puji Astuti; Abdul Azis; Testiana Deni Wijayatiningsih; Sri Susilowati Sumarti; Dwi Anggani Lingga Barati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The fair level of teacher UKG results indicates the need for exploration of the content knowledge of pre-service teachers. The purpose of this study focuses onthe exploration of content knowledge of chemistry students on the material of theperiodic elements system to prepare professional teachers. The research usedwas pre-experimental design using one-shot case study design. Data collectiontechniques in this study are test techniques, observation techniques, and openinterviews. The data collection instruments in this research is a sheet of periodicelement system at high school level to test readiness of pre-service teachers inconducting internship practice at partner schools. This test is part of the threeindicators of Content Knowledge: Knowledge of disciplinary content, knowledgethat alternative frameworks for thinking about the content exist and knowledge ofthe relationship between big ideas and supporting ideas in a content area. Theresults showed that the average content of teacher candidate knowledge on thematerial of the periodic element system is 51. Keywords: content knowledge, UKG, Sistem periodik unsur.